Making Merit, Making Art A Thai Temple in Wimbledon - Cate, Sandra (University of Hawaii Press, 2002)
Sandra Cate's pioneering ethnography of art-making at Wat Buddhapadipa, a Thai Buddhist temple in Wimbledon, England, explores contemporary art at the crossroads of identity, authority, and value. Between 1984 and 1992, twenty-six young Thai artists painted a series of temple murals that continue to attract worshippers and tourists from around the world. Their work, both celebrated and controversial, depicts stories from the Buddha's lives in otherworldly landscapes punctuated with sly references to this-worldly politics and popular culture. Schooled in international art trends, the artists reverse an Orientalist narrative of the Asian Other, telling their own stories to diverse audiences and subsuming Western spaces into a Buddhist worldview.In her investigation of temple murals as social portraiture, Cate looks at the ongoing dialectic between the "real" and the "imaginary" as mural painters depict visual and moral hierarchies of sentient beings. As they manipulate indigenous notions of sacred space and the creative process, the Wat Buddhapadipa muralists generate complex, expansive visions of social place and identity